Challenges and Pitfalls: Performing Clinical Trials in Patients With Congenital Diaphragmatic Hernia - Cochius - den Otter, Suzan; Deprest, Jan A.; Storme, Laurent; Greenough, Anne; Tibboel, Dick (Frontiers in Pediatrics, 2022)
Congenital diaphragmatic hernia (CDH) is a rare developmental defect of lungs and diaphragm, with a substantial morbidity and mortality. Although international established treatment guidelines have been developed, most recommendations are still expert opinions. Trials in patients with CDH, more in particular randomized controlled trials, are rare. Only 3 multicenter trials in patients with CDH have been completed, which focused on fetoscopic tracheal occlusion and ventilation mode. Another 4 are currently recruiting, two with a focus on perinatal transition and two on the treatment of pulmonary hypertension. Herein, we discuss major challenges and pitfalls when performing a clinical trial in infants with CDH. It is essential to select the correct intervention and dose, select the appropriate population of CDH patients but also define a relevant endpoint that allows a realistic duration and sample size. New statistical approaches might increase the feasibility of randomized controlled trials in patients with CDH. One should also timely perform the trial, when there is still equipoise. But above all awareness of policy makers for the relevance of investigator-initiated trials is essential for future clinical research in this rare disease.